2003
DOI: 10.1093/nar/gkg283
|View full text |Cite
|
Sign up to set email alerts
|

Absolute mRNA concentrations from sequence-specific calibration of oligonucleotide arrays

Abstract: Oligonucleotide microarrays are based on the hybridization of labeled mRNA molecules to short length oligonucleotide probes on a glass surface. Two effects have been shown to affect the raw data: the sequence dependence of the probe hybridization properties and the chemical saturation resulting from surface adsorption processes. We address both issues simultaneously using a physically motivated hybridization model. Based on publicly available calibration data sets, we show that Langmuir adsorption accurately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 9 publications
6
159
0
Order By: Relevance
“…Therefore, although the different available microarray platforms for mRNA expression profiling have been extensively evaluated (Canales et al 2006), there is still no gold standard for quantifying mRNA transcript concentrations by microarrays. The approaches developed so far encompass mathematical modeling (Hekstra et al 2003;Frigessi et al 2005), calibrated reference samples (Dudley et al 2002), exogenous RNA controls (Carter et al 2005b), and combinations of mathematical modeling and spike measurements (Zhao et al 2007). The TransCount method (Frigessi et al 2005) is based on Bayesian statistical modeling and utilizes covariants of the microarray experiment to calculate the concentration from the signal intensity of each probe.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the different available microarray platforms for mRNA expression profiling have been extensively evaluated (Canales et al 2006), there is still no gold standard for quantifying mRNA transcript concentrations by microarrays. The approaches developed so far encompass mathematical modeling (Hekstra et al 2003;Frigessi et al 2005), calibrated reference samples (Dudley et al 2002), exogenous RNA controls (Carter et al 2005b), and combinations of mathematical modeling and spike measurements (Zhao et al 2007). The TransCount method (Frigessi et al 2005) is based on Bayesian statistical modeling and utilizes covariants of the microarray experiment to calculate the concentration from the signal intensity of each probe.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 For example, Corn and co-workers fit thermodynamic data for probes on planar Au to a Langmuir isotherm and report similar K d values (55 nM for an 18-mer probe/target duplex in a 300 mM NaCl, 100 mM urea PBS buffer). 57 Peterson et al found that perfectly matched duplex formation on an Au surface could be fit to a Langmuir isotherm (with K d =17 nM for a 25-mer duplex in 1 M NaCl buffer), while mismatched duplexes were better modeled by the Sips isotherm.…”
Section: Nanowire Mb Assay Sensitivitymentioning
confidence: 94%
“…Whereas the former results were based on the outcome of hybridization experiments only, thermodynamics has been taken into account in several other studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Indeed, hybridization of nucleotide molecules in solution is a well understood biophysical process driven by thermodynamics 20 .…”
Section: Introductionmentioning
confidence: 99%